2008
DOI: 10.1007/s10195-008-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Femoral neck fracture following intramedullary nailing with misplacement of an end cup: report of two cases

Abstract: Femoral neck fracture is an unusual complication of intramedullary fixation of a broken femur. We report on two cases of femoral neck fractures attributed to misplacement of an end cup and subsequent invasive maneuvers in an effort to remove it. Iatrogenic fractures of the femoral neck during or after intramedullary nailing are reported in the medical literature. Authors associate it with many possible technical mistakes performed during the procedure, yet no complications after missed end cup placement were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…2 This procedure requires experience, and patients with femoral neck fractures after IMIL nailing are described by several authors. 3 Treatment of isolated femur neck fractures are often performed with open or closed reduction with cannulated cancellous screw fixation. 4 With an antegrade femoral nail in situ, it complicates the fixation of neck of femur fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This procedure requires experience, and patients with femoral neck fractures after IMIL nailing are described by several authors. 3 Treatment of isolated femur neck fractures are often performed with open or closed reduction with cannulated cancellous screw fixation. 4 With an antegrade femoral nail in situ, it complicates the fixation of neck of femur fracture.…”
Section: Discussionmentioning
confidence: 99%
“…6 The reasons for an iatrogenic neck fracture during femoral nail include The forceful use of an awl in wrong direction, multiple entry points in greater trochanter may weaken neck of femur such that subsequent insertion of the nail completes the fracture and hammering of the nail insertion jig. 3 Khan et al conducted a study wherein authors observed good functional outcomes in patients who sustained iatrogenic neck fractures while IMIL nailing of femoral shaft fractures, that were treated conservatively. 7 Various factors influence healing process of neck fractures and management depends of the surgeon's preference.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also reports of iatrogenic femoral neck fractures during femoral IM nailing [6,17]. Grala et al [18] reported two cases of femoral neck fractures after misplaced nail end caps and their unsuccessful manoeuvres to retrieve those. Finally, Grimme et al [7] presented one case of a medial femoral condyle fracture during extraction of a retrograde IM femoral nail.…”
Section: Discussionmentioning
confidence: 99%